2008
DOI: 10.4137/bmi.s1173
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in Hair Follicle Dermal Papilla Cells after Treatment with Stanozolol

Abstract: Doping with anabolic agents is a topic in sports where strength is crucial, e.g. sprinting, weight lifting and many more. Testosterone and its functional analogs are the drugs of choice taken as pills, creams, tape or injections to increase muscle mass and body performance, and to reduce body fat. Stanozolol (17β-hydroxy-17α-methyl-5α-androst-2-eno[3,2c]pyrazol) is a testosterone analogue with the same anabolic effect like testosterone but its ring structure makes it possible to take it orally. Therefore, stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Toma et al demonstrated that small punch biopsies of human scalp proliferate in response to SKP medium supplemented with FGF2 and EGF (Toma et al, 2005). Dermal papilla cells derived from hair follicle show higher proliferative property in AmnioMAX C-100 or HFDPC growth medium compared to 10% FBS-DMEM (Driskell et al, 2012;Reiter et al, 2008). In our study, we demonstrated that SKP medium exhibited higher expression level of dermal progenitor genes compared to other culture media, indicating that SKP medium is appropriate for preserving the stemness of hDSPCs (Fig.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Toma et al demonstrated that small punch biopsies of human scalp proliferate in response to SKP medium supplemented with FGF2 and EGF (Toma et al, 2005). Dermal papilla cells derived from hair follicle show higher proliferative property in AmnioMAX C-100 or HFDPC growth medium compared to 10% FBS-DMEM (Driskell et al, 2012;Reiter et al, 2008). In our study, we demonstrated that SKP medium exhibited higher expression level of dermal progenitor genes compared to other culture media, indicating that SKP medium is appropriate for preserving the stemness of hDSPCs (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…During in vitro culture, hDSPCs, which exhibited stem celllike characteristics in our previous study, gradually lose the expression of transcription factors associated with multipotency and self-renewal, such as SOX2 and NANOG for maintaining the characteristics of stem cells. Several previous reports suggested that the quality of the stem cells strongly depend on the culture method (Driskell et al, 2012;Grayson et al, 2007;Kuroda et al, 2010;Minchenko et al, 1994;Reiter et al, 2008;Ren et al, 2006;Rendl et al, 2005). Thus, we investigated whether hDSPCs retain their stemness in various culture conditions despite long-term culture.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…To date most research has been in diseases involving skin conditions (Ohyama et al, 2006). However, hair follicles are also being examined for markers in to quantify exposures to pharmaceuticals (Reiter et al, 2008) or toxicology to certain drug targets (Kim et al, 2006).…”
Section: Hair Folliclesmentioning
confidence: 99%
“…Cells were harvested at different time points after treatment, RNA was extracted, and gene expression analysis was done via RT‐qPCR for quantifying 13 different genes. Genes like the androgen receptor (AR), the apoptosis factors Fas receptor (FasR) and caspase 8, the fibroblast growth factor FGF7 and the 5α‐Steroidreductase SRD5A2 were detected as significantly regulated, whereas only AR and FasR were significantly regulated in both female and male cells and the other genes were significantly regulated either in female (FGF7, Caspase 8) or in male cells (SRD5A2) 37. In another study, the expression of different genes in plucked hair follicle samples was quantified in female and male hair follicles and also in a small number of hair samples from weightlifters under doping conditions.…”
Section: Effects Of Androgens On Human Hair Folliclementioning
confidence: 99%